The Active Covid-19 Infection and Cancer Management - Iqbal Memon, Amir; Masroor Bhatti, Aisha; Naz, Tarnum; Khan, Ramsha; Bano, Sahira; Batool, Nida; Ali Shah, Syed Zulfiquar (Pakistan Journal of Medical & Health Sciences, 2022)
Though the life has been totally changed after the covid-19 pandemic and one has never imagined being in such circumstances. The face mask was once thought to be the beauty for operating surgeons is now globally indicated to be prevented from the covid-19 infection. Every aspect of life has been affected by the pandemic including the routine hospital services for the elective cases.1As the evolution is the part of life so we all are growing to make our life adjustable with it. No doubt the prevention and protection is the key to survive but along with that one should have courage to fight with it. Hence it is an unpleasant and life threatening disease and also very distressing for the one who became its victim.2 Globally the covid-19 pandemic has an alarming effects on the precious lives and its causing huge challenges to the everyday routine3. By the April 2020, globally more than 8 lac cases of covid-19 has recorded. As the cancer patients are already immune compromised and more prone to get contacted with covid-19 infection, as is supported by a Chinese study that they are more vulnerable to develop complications as well4,5. When a cancer patient simultaneously contacted by the covid-19 infection then the treatment should be prioritize that which patient can be delayed until the control over active infection can occur. Though the risk of transmission to the health care workers (HCW) is significant while treating such patients.6As there should be a balanced practice for the management of covid-19 pandemic and for the cancer patients and being HCW we need to cover both the diseases at the same time to save the precious lives. There are international guidelines to manage the cancer patients during covid-19 pandemic but the decision is still vary from patient to patient according to the stage of the cancer and also the severity of covid-19 infection. It has been observed that multi-disciplinary approach plays the major role for the cancer patient management including surgeons along with the oncologist, radiologist, pathologist, psychiatrist, councilor and nurse. Meanwhile they all are facing the major risk of being contacted to the covid-19 when their patients are being the victim of it7.